2006
DOI: 10.1677/joe.1.06396
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of muscle glucose uptake by the vasopeptidase inhibitor, omapatrilat, is independent of insulin signaling and the AMP kinase pathway

Abstract: Omapatrilat (OMA), a vasopeptidase inhibitor (VPI), presently being tested in clinical trials for its antihypertensive properties, inhibits both angiotensin-converting enzyme and neutral endopeptidase, and raises tissue bradykinin levels. Recent studies from our laboratory and those of others have demonstrated that VPIs enhance muscle glucose uptake in animal models, and this effect is mediated by the bradykinin-nitric oxide pathway. The mechanism of the effect of OMA on muscle glucose uptake, however, is pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…In a similar independent study it was found that Omapatrilat, a vasopeptidase inhibitor, induced insulin sensitization and increased myocardial glucose uptake in obese Zucker rats and that the effect of Omapatrilat was greater than Ramipril in part due to stimulation of the B 2 receptor (Wang, et al 2003). Later this group reported that treatment of obese Zucker rats with a vasopeptidase inhibitor increased muscle glucose uptake independent of insulin signaling (Wong, et al 2006). In two of these studies protection of bradykinin from degradation by neutral endopeptidase was found to improve insulin action (Arbin, et al 2001; Wang, et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In a similar independent study it was found that Omapatrilat, a vasopeptidase inhibitor, induced insulin sensitization and increased myocardial glucose uptake in obese Zucker rats and that the effect of Omapatrilat was greater than Ramipril in part due to stimulation of the B 2 receptor (Wang, et al 2003). Later this group reported that treatment of obese Zucker rats with a vasopeptidase inhibitor increased muscle glucose uptake independent of insulin signaling (Wong, et al 2006). In two of these studies protection of bradykinin from degradation by neutral endopeptidase was found to improve insulin action (Arbin, et al 2001; Wang, et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In a similar independent study it was found that Omapatrilat, a vasopeptidase inhibitor, induced insulin sensitization and increased myocardial glucose uptake in obese Zucker rats and that the effect of Omapatrilat was greater than Ramipril in part due to stimulation of the B 2 receptor [33]. Later this group reported that treatment of obese Zucker rats with a vasopeptidase inhibitor increased muscle glucose uptake independent of insulin signaling [34]. In two of these studies protection of bradykinin from degradation by NEP was found to improve insulin action [32, 33].…”
Section: Discussionmentioning
confidence: 99%
“…The natriuretic peptides are also degraded by NEP [36]. Because NEP is expressed in skeletal muscle in relatively large amounts and being located on the cell surface, NEP is able to hydrolyze peptides in the vicinity of their receptors thereby neutralizing their bioactivity [34, 36]. However, inhibition of ACE may also lead to protection of bradykinin levels by inhibiting kininase-II-mediated degradation of this nonapeptide [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the index of purity of both fractions were O90%. Homogenization of muscle (Wong et al 2006) and fat (Beard et al 2006) samples was performed as described previously. The protein concentration in all samples was determined by the detergent-compatible modified Lowry microassay, using a standardized assay kit.…”
Section: Immunoprecipitation and Western Blot Analysismentioning
confidence: 99%